ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL PADA LAPORAN KEUANGAN PT. BANK SYARIAH INDONESIA TBK TAHUN 2019-2023 - Yuriani, Ima; Andre Agustianto, Mochammad (Politeknik Bisnis Indonesia, 2024)
This study was conducted because it is very important for financial institutions to maintain their financial health, especially Islamic banks. The purpose of this study is to determine the health level of PT. Bank Syariah Indonesia (BSI) Tbk in 2019-2023. The assessment indicators used in this study are Capital, Asset Quality, Management, Earning, and Liquidity or abbreviated as CAMEL. The Camel method is a factor that greatly determines the health of a bank. This study was conducted with a quantitative descriptive approach, namely using secondary data obtained from the annual Financial Report published on the company's official website, by analyzing the CAR, NPF, PDN, ROA, ROE, BOPO, NI, and FDR ratios. The results of the study showed that the CAR ratio in the 2019-2023 period received the predicate